Ritual Circumcisions of Minors: Civil and Criminal Perspectives (Stato, Chiese e pluralismo confessionale, 2021)
SUMMARY: 1. Introduction - 2. Parental authority and the inherent rights of the minor. The best interests of the minor - 2.1. Conflicting rights. The current understanding of parental authority - 2.2. Limits to parental authority. Personality rights - 2.3. The minor’s consent in surgical procedures - 2.4. Circumcision and the best interests of the minor. An act which falls within parental authority? - 3. Criminal responsibility in acts of circumcision for religious motives - 3.1. The criminal approximation to female genital mutilation - 3.2. Circumcision in criminal jurisprudence - 4. Concluding remarks. De iure condendo contributions.